Improving value chains of selected underutilized crops for the economic well-being of smallholder farmers in South-Eastern Sri Lanka - Bandula, Hambange Don Arosh Chamikara (2021)
Underutilized crops are widely recognized for their socio-economic, nutritional, and agrobiodiversity values. Studies on underutilized crop farming systems and value chains in Sri Lanka are limited. The research had been undertaken to investigate the underutilized crops in smallholder farming systems, economic contributions, and existing value chains. Primary data were collected from 30 Gramaniladari divisions (GN Divisions) located in twelve Divisional Secretariat (DS) from Uva and Eastern administrative provinces of Sri Lanka. A summary of the different chapters is presented below.